Influence of fiber characteristics of Nigérian grown Bambusa vulgaris Schrad on its relative density and burst strength (2008)
Strength properties of Bambusa vulgaris with increasing culm height was studied considering its fiber characteristics with particular reference to the presence or absence of nodes. At the interaode. an increase in fiber length with increasing culm height (2.78 mm-3.73 mm from base to lop) was observed, while fiber diameter behaved conversely, showing a reduction from base to top (0.033 mm-0.013 mm). Relative density and burst strength had a similar trend as they both showed reduction in values from base to top (0.62-0.31 and 8.2KN/mmJ - 5.3KN/mnr respectively). At the node, reduction in fiber length from base to top (1.79 mm 1.39 mm) was ohserved. while fiber diameter increased from base to top (0.023 mm-0.031mm). Relative density showed a reduction from base to lop (0.64-0.32). while burst strength had a similar trend having a range of above 1 IKN/mm5-5.4KN/mmJ from base to top Statistical analysis of the data from the node revealed a strong direct correlation between fiber length and relative density, while fiber diameter showed a weak and inverse relationship. Burst strength showed a direct but weak relationship with fiber length, while it had an inverse and weak correlation with fiber diameter. At the intemode. a weak and inverse relationship was revealed between density and fiber length, while fiber diameter showed a direct but weak relationship. Burst strength and fiber length showed a strong but inverse correlation, while fiher diameter and burst strength revealed a direct and significant correlation.